2023
DOI: 10.1111/nph.19002
|View full text |Cite
|
Sign up to set email alerts
|

Root cap is an important determinant of rhizosphere microbiome assembly

Abstract: Plants impact the development of their rhizosphere microbial communities. It is yet unclear to what extent the root cap and specific root zones contribute to microbial community assembly.To test the roles of root caps and root hairs in the establishment of microbiomes along maize roots (Zea mays), we compared the composition of prokaryote (archaea and bacteria) and protist (Cercozoa and Endomyxa) microbiomes of intact or decapped primary roots of maize inbred line B73 with its isogenic root hairless (rth3) mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 156 publications
0
8
0
Order By: Relevance
“…The underlying mechanisms currently include (i) competition for niche space, which directly determined whether the beneficial rhizosphere microbiome successful colonization on the root surface [ 9 , 14 , 25 ],(ii) inhibition from secondary metabolites, which determined metabolite exchange networks between rhizosphere microbiome and plant roots via potential allelopathy effect [ 41 , 58 ],(iii) regulation of gene expression in plants, which would affected plant hormone signal transduction and immune system activities (tolerance or avoidance) via the process of microbial inheritance in plants [ 1 , 38 ]. Furthermore, pioneer studies indicated that root hairs are able to influence the rhizosphere microbiome assemblage, and in turn rhizosphere microbes are able to interact with plant-modifying root hairs [ 34 , 55 ]. Root hairs have physical properties that play vital roles in the two-way interaction by specifically changing the plant–microbe interaction interface [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms currently include (i) competition for niche space, which directly determined whether the beneficial rhizosphere microbiome successful colonization on the root surface [ 9 , 14 , 25 ],(ii) inhibition from secondary metabolites, which determined metabolite exchange networks between rhizosphere microbiome and plant roots via potential allelopathy effect [ 41 , 58 ],(iii) regulation of gene expression in plants, which would affected plant hormone signal transduction and immune system activities (tolerance or avoidance) via the process of microbial inheritance in plants [ 1 , 38 ]. Furthermore, pioneer studies indicated that root hairs are able to influence the rhizosphere microbiome assemblage, and in turn rhizosphere microbes are able to interact with plant-modifying root hairs [ 34 , 55 ]. Root hairs have physical properties that play vital roles in the two-way interaction by specifically changing the plant–microbe interaction interface [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…For comparison, we also imaged the root cap, which has been shown to be the first point of contact for bacterial cells attempting to colonize the root 36 . Additionally, the root cap may act as a filter that prevents further microbial colonization in the root 37 .…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, malfunctions within regulated cell death in mammal gut epithelial cells produce death-induced nutrient release (DINNR) that can fuel bacterial growth and infection and could cause a variety of disorders such as inflammatory diseases 34 . The importance of an intact root cap in plant-microbe interactions is further highlighter by the fact that the physical removal of root caps in maize plants leads to increased colonization of the root tip by the plant growth promoting rhizobacterium (PGPR) Pseudomonas fluorescens 35 and to changes in the rhizosphere microbiome composition along the root axis 36 . Moreover, it has been suggested that border cells released from the root cap may distract root-feeding nematodes from attacking plant roots 37 .…”
Section: Discussionmentioning
confidence: 99%